2015
DOI: 10.1002/cctc.201500488
|View full text |Cite
|
Sign up to set email alerts
|

Black Titania for Superior Photocatalytic Hydrogen Production and Photoelectrochemical Water Splitting

Abstract: To utilize visible‐light solar energy to meet environmental and energy crises, black TiO2 as a photocatalyst is an excellent solution to clean polluted air and water and to produce H2. Herein, black TiO2 with a crystalline core–amorphous shell structure reduced easily by CaH2 at 400 °C is demonstrated to harvest over 80 % solar absorption, whereas white TiO2 harvests only 7 %, and possesses superior photocatalytic performances in the degradation of organics and H2 production. Its water decontamination is 2.4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 44 publications
2
57
0
1
Order By: Relevance
“…Solution A (tetrabutyl titanate/EtOH) and solution B (HNO 3 /EtOH) were mixed to form a sol, followed by adding of a certain amount of NaBH 4 until it reconstituted into a gel. [ 50 ] The resulted black TiO 2 nanoparticles could harvest over 80% solar absorption (Figure 8 b). [ 58 ] Hundred-gram grade of black TiO 2 nanoparticles have been successfully produced by NaBH 4 reduction through dry process, corresponding pictures were shown in Figure 8 a.…”
Section: Hydrogen Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution A (tetrabutyl titanate/EtOH) and solution B (HNO 3 /EtOH) were mixed to form a sol, followed by adding of a certain amount of NaBH 4 until it reconstituted into a gel. [ 50 ] The resulted black TiO 2 nanoparticles could harvest over 80% solar absorption (Figure 8 b). [ 58 ] Hundred-gram grade of black TiO 2 nanoparticles have been successfully produced by NaBH 4 reduction through dry process, corresponding pictures were shown in Figure 8 a.…”
Section: Hydrogen Reductionmentioning
confidence: 99%
“…Black TiO 2 nanoparticles could be obtained by annealing amorphous TiO 2 under H 2 fl ow at 500 °C for 1h, followed by cooling in an inert environment to room temperature with a rate of approximately 50 °C/min (optical absorption shown in Figure 5 a). In this aspect, hydrides, such as NaBH 4 , [ 48 ] N 2 H 4 , [ 49 ] CaH 2 , [ 50 ] which can be decomposed to generate molecular hydrogen at mild experimental (101). [ 39 ] Besides the amorphous TiO 2 , protonated titanate could be effi ciently converted to dark brown H-doped TiO 2 (TiO 2 -H) by heating under a fl ow of H 2 (5% in N 2 ) at 500 °C.…”
Section: Hydrogen Reductionmentioning
confidence: 99%
“…Color change from white to black for TiO 2 nanomaterials reflects the change in optical properties and thus suggests the structural change after modification, at least the surface structural change. High-resolution transmission electron microscope (HRTEM) has revealed that a number of black TiO 2 nanomaterials have a crystalline/ amorphous core/shell structure, while white ones have clear lattice fringes throughout the crystals [22,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The amorphous or disordered surface layer has been considered the typical feature of black TiO 2 nanomaterials.…”
Section: Basic Properties Of Black Tio 2 Versusmentioning
confidence: 99%
“…[83,84]) by CaH 2 usually generates black Ti 2 O 3 rather than black TiO 2 [83,84]. Recently, black TiO 2 was prepared from Degussa P25 by CaH 2 reduction at 400°C [42]. The black TiO 2 had a crystalline/amorphous core/shell structure with abundant oxygen vacancies, which led to a high solar absorption (~81% solar energy absorption) and significantly enhanced photocatalytic organic degradation and water-splitting performance [42].…”
Section: Black Tio 2 Nanomaterials As Visible Light-active Photocatalmentioning
confidence: 99%
“…Only T600 possesses low light absorption in UV region, as the presence of Al in the sample may contribute to the decreased light absorption behavior. The relation of colored TiO2 with the enhancement of light absorption properties in visible light range in different methods and morphologies were also reported in several papers [9,[13][14][15][16].…”
Section: Uv-vis Diffuse Reflectance Spectramentioning
confidence: 66%